Bad to good : achieving high quality and impact in your research - Woodside, Arch G. (United Kingdom : Emerald, 2016)
Bad to Good: Achieving High Quality Impact in Your Research covers 24 common bad practices in theory construction and empirical testing and provides readers with the tools to turn these into good practices. For decades, scholars have bemoaned the low relevancy and impact of most research in the leading journals in business, management, and marketing. The majority of the research that gets published, perhaps 70% of it, hardly has any measurable scholarly impact in terms of citations. Rather than low relevancy, this book speculates that the deeper issue is the pervasive use of bad research practices appearing in most articles in almost all ranked journals in the sub-disciplines of business. --
Moving away from bad practices in research toward constructing useful theory and doing useful research ; Embrace complexity theory, perform contrarian case analysis, and model multiple realities ; Moving beyond multiple regression analysis and symmetric tests to algorithms and asymmetric tests / Arch G. Woodside -- Case-based modeling of business-business relationships / Arch G. Woodside and Roger Baxter -- Performing triple sensemaking in field experiments / Arch G. Woodside, Alexandre Schpektor and Richard Xia -- Complexity theory, configural analysis, and deepening the service dominant logic / Pei-Ling Wu, Shih-Shuo Yeh, Tzung-Cheng (T.C.) Huan and Arch G. Woodside -- Complexity theory and human resources management: transcending variable and case-based perspectives of service employees' (un)happiness and work performance / Chyi Jaw, James Po-Hsun Hsaio, Tzung-Cheng (T.C.) Huan and Arch G. Woodside.
(3eTJQjGJ eYQV GdbGgQI GdOhdj ddcJGH (B2020s
Includes bibliographical references and index.
Keywords: Business -- Research -- Methodology